THE INFLUENCE OF DAR, ROE AND COMPANY SIZE ON EPS (FOOD AND BEVERAGE SUB SECTOR COMPANIES IN BEI 2024) - Riko Sutriyadi; Nur Haris Ependi; Maria Evy Purwitasari; Sudirman (ASIAN PUBLISHER, 2025)
The capital market acts as a source of funding for companies as well as an investment platform that includes various instruments such as stocks, bonds, and mutual funds. The existence of the capital market provides an opportunity for companies to obtain capital that can be used in business development. Stock prices are the main indicator in reflecting the company's performance, which is influenced by internal factors such as financial statements, profitability, as well as external factors such as economic conditions, government policies, and the global market situation. Investors need to understand the risks of stock investment, including price volatility, and consider various factors in decision making in order to maximize profits while increasing company value. This research uses a quantitative descriptive method with data from the Indonesia Stock Exchange. The results showed that partially and simultaneously, Debt to Assets Ratio (DAR), Return on Equity (ROE), and company size affect stock prices with a contribution of 36%.